2008
DOI: 10.1007/s11552-008-9091-5
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Use as an Adjunctive Modality in a Patient with Multiple Flexor Tendon Ruptures

Abstract: Botulinum toxin A has been described in treatment protocols for several disease processes, from primary axillary hyperhydorosis to esophageal dysfunction. It is best known for its use in plastic and dermatological practices. Botulinum toxin has a straightforward mechanism of action. The toxin inhibits acetylcholine release at the neuromuscular junction causing a chemical denervation, which ceases contractions of the muscle. With its minimal side effect profile, botulinum toxin should be considered when muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The optimal timing for perioperative BoNT is unknown, but different studies have described preoperatively up to 5 weeks presurgery, 6 , 13 , 14 intraoperatively during the surgery, 5 , 15 and postoperatively as early as 1 week post surgery. 19 Our cases demonstrate an important role for perioperative BoNT in patients with spasticity undergoing surgical interventions where their spasticity could affect the surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal timing for perioperative BoNT is unknown, but different studies have described preoperatively up to 5 weeks presurgery, 6 , 13 , 14 intraoperatively during the surgery, 5 , 15 and postoperatively as early as 1 week post surgery. 19 Our cases demonstrate an important role for perioperative BoNT in patients with spasticity undergoing surgical interventions where their spasticity could affect the surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies have suggested that perioperative BoNT administration (the perioperative period includes the following 3 time frames: preoperative, intraoperative, or postoperative) 12 may reduce pain, spasticity, and analgesic use in patients with preexisting spasticity. 5 , 6 , 13 , 14 , 15 Similarly, patients undergoing orthopedic procedures unrelated to their spasticity, such as hip replacement for hip dysplasia, wound flap surgery for pressure ulcers, or neck stabilization for cervical myelopathy, may also benefit from perioperative BoNT injections to help with a successful surgical outcome. 5 , 6 , 7 , 16 , 17 , 18 …”
mentioning
confidence: 99%
“…The primary analgesic effect of BoNT-A is suggested to result from easing the tension in the whole enthesis site, including the tendon [36], thereby resulting in immobilisation of the enthesis. This procedure has been shown to improve the healing process of several tendons [40] [41]. BoNT-A is also said to have an analgesic effect by inhibiting the release of neurotransmitters such as glutamate, substance P and calcitonin gene-related peptide involved in the transmission of tendon pain [42].…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative BoNT injection has also led to a reduction of pain and spasticity and a decrease in analgesic use in patients undergoing surgery on their spastic limbs. 17 , 18 , 19 , 20 , 21 Perioperative BoNT injections can also optimize surgical outcomes of patients with spasticity undergoing orthopedic procedures not directly related to their preexisting spasticity, 11 , 17 , 18 , 19 , 20 , 21 , 22 Perioperative BoNT could therefore help improve surgical outcomes, alleviate postoperative pain, and facilitate rehabilitation participation. 11 …”
mentioning
confidence: 99%